KADAR UREUM DAN KREATININ PADA ANAK SEKOLAH DASAR DI DEKAT PERTAMBANGAN EMAS SKALA KECIL DESA RANGAN TATE KABUPATEN GUNUNG MAS - Putri, Selviana; Arfah Safitri, Nazwa; Purbayanti, Dwi (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2025)
Background: Children living near artisanal and small-scale gold mining (ASGM) areas are at risk of exposure to hazardous chemicals, particularly mercury, which is known to be nephrotoxic. This study aimed to describe urea and creatinine levels as indicators of kidney function in children residing in ASGM areas. Method: The study employed a descriptive-analytic design with a cross-sectional approach. The sample consisted of 49 students from grades IV–VI of Rangan Tate Public Elementary School, selected using a total sampling technique. Data were collected through questionnaires, urea measurement using the Berthelot method, and creatinine measurement using the kinetic Jaffe method. Both methods are simple, fast, and inexpensive, although they require automated instruments for better precision. Data were analyzed descriptively and with Spearman correlation tests using SPSS version 30 (p<0.05). Result: The results showed that all respondents’ urea levels were within the normal range (11–39 mg/dL) with a mean of 28.3 mg/dL. In contrast, 69.4% of respondents had creatinine levels above the reference range (0.3–0.7 mg/dL), with a mean of 0.79 mg/dL. A significant correlation was found between children’s involvement in mining activities and creatinine levels (r=0.406; p=0.004), while no significant associations were observed between other variables and either urea or creatinine levels. A total of 8% of children were reported to participate in gold mining activities, and 20.4% lived within a radius of less than 1 km from mining sites. Conclusion: The increase in creatinine levels among most children living near ASGM areas indicates a potential risk of impaired kidney function. Further monitoring using more sensitive and accurate biomarkers is recommended for early detection of nephrotoxic effects.